Occurrence of Norovirus GI in green and red onion - Mohd Sahroni, Noor Hidayah; Tuan Chilek, Tuan Zainazor; Pui, Chai Fung; Ahmad, Noorlis; Mat Radzi, Noor Eliza; Mohamed Dasuki, Naziehah; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Several Norovirus cases due to consumption of green onions have been reported during recent years but reports on red onions are not found. Onions are one of the major tastes in Malaysian food which are sometimes consuming raw especially the green onion. Viral contamination in onions can occur due to planting condition and not properly prepared food. This situation can pose the human health risk. A method was developed to detect the Norovirus that might present on different type of onions. In this study, 60 samples were collected from local market. Elution by Tryptose Phosphate Glycine broth and concentration steps using negatively charge filter were applied to enhance the detection of virus in food due to low copies of virus on food surface. The viral RNA was extracted using Qiagen Rneasy Mini kit before further detection using One-step RT-PCR. The total incidence of Norovirus in green onion and red onion was 13.33% (4/30) and 3.33 % (1/30) respectively. This is the first report of the detection of Norovirus in red and green onions in Malaysia. Based on the results, it is concluded that this method is reliable to detect Norovirus on onions and vegetables surface and hence can be applied in the laboratories for routine or food borne outbreak investigation.